First results with the ANET Compact Thermal Neutron Collimator. (19th November 2021) - Sans-Planell, O.; Costa, M.; Durisi, E.; Mafucci, E.; Menzio, L.; Monti, V.; Visca, L.; Grazzi, F.; Bedogni, R.; Altieri, S.
Abstract: This paper presents the first determination of the spatial resolution of the ANET Compact Neutron Collimator, obtained with a measuring campaign at the LENA Mark-II TRIGA reactor in Pavia. This novel collimator consists of a sequence of collimating and absorbing channels organised in a chessboard-like geometry. It has a scalable structure both in length and in the field of view. It is characterized by an elevated collimation power within a limited length. Its scalability and compactness are added values with respect to traditional collimating system. The prototype tested in this article is composed of 4 concatenated stages, each 100 mm long, with a channel width of 2.5 mm, delivering a nominal L/D factor of 160. This measuring campaign illustrates the use of the ANET collimator and its potential application in neutron imaging for facilities with small or medium size neutron sources.